Estimating New Keynesian Import Price Models - Ida Wolden Bache; Bjørn E. Naug (Norges Bank, 2007)
We estimate a range of New Keynesian import price models for Norway and the UK. Contrary to standard pass-through regression analysis, this approach allows us to make a distinction between the parameters in theoretical price-setting rules and parameters in the expectations mechanisms. We find positive and significant effects of expected future import price growth for Norway. The estimates for the UK do not lend much support to the hypothesis that pricesetting rules are forward-looking. For both countries, the results favour a specification that incorporates both local- and producer currency pricing, but no effect of lagged import price growth. We find mixed evidence of pricing-to-market: only for the UK do the results suggest a role for domestic prices or costs in explaining import prices.
hdl:11250/2498257
Keywords: C32; C52; F41; 330; GMM; New Keynesian open economy models; import prices; exchange rate pass-through